Hubungan Faktor Individu Dan Lingkungan Dengan Higiene Sanitasi Makanan Pada Siswa SMP Penerima MBG - Mirza Fathan Fuadi (Indonesian Journal of Health Community, 2026)
Food safety is an important aspect of the Free Nutritious Meal Program (MBG). This study aimed to examine the association between individual and environmental factors and the implementation of food hygiene and sanitation practices among junior high school students in Semarang who received MBG meals from SPPG Yayasan Bina Bangsa Semarang. This study employed a quantitative design with a cross-sectional approach. The data were obtained from 101 students receiving MBG meals at three junior high schools, selected using purposive sampling. The individual factors examined in this study included knowledge and attitudes, while the environmental factors consisted of handwashing facilities, exposure to food safety information, and peer support. The dependent variable was the implementation of food hygiene and sanitation practices. Data were analyzed using univariate and bivariate analyses, with the chi-square test applied at a significance level of 0.05. The results showed significant associations between the implementation of food hygiene and sanitation practices and knowledge (p=0.001), attitudes (p=0.001), handwashing facilities (p=0.001), exposure to food safety information (p=0.009), and peer support (p=0.007). Therefore, both individual and environmental factors were associated with the implementation of food hygiene and sanitation practices among students receiving MBG meals.